Gendering and Diversifying Trade Union Leadership. - Ledwith, Sue (Routledge research in employment relations., 2012)
Examining the experiences of leadership among trade unionists in a range of unions and labor movements around the world, this volume addresses perspectives of women and men from a range of identities such as race/ethnicity, sexuality, and age. It analyses existing models of leadership in various political organizational forms, especially trade unions, but also including business and management approaches, leadership forms which arise from fields such as community, pedagogy, and the third sector. This book analyzes and critiques concepts, expectations, and experiences of union leaders.